Is there benefit to continue magnesium sulphate postpartum in women receiving magnesium sulphate before delivery? A randomised controlled study. (11th July 2018) - Vigil‐DeGracia, P; Ludmir, J; Ng, J; Reyes‐Tejada, O; Nova, C; Beltré, A; Yuen‐Chon, V; Collantes, J; Turcios, E; Lewis, R; Cabrera, S
Abstract : Objective: To determine if the use of magnesium sulphate postdelivery reduces the risk of eclampsia in women with severe pre‐eclampsia exposed to at least 8 hours of magnesium sulphate before delivery. Design: Randomised multicentre controlled trial. Setting: Latin America. Population: Women with severe pre‐eclampsia that had received a 4‐g loading dose followed by 1 g per hour for 8 hours as maintenance dose before delivery. Methods: In all, 1113 women were randomised; 555 women were randomised to continue the infusion of magnesium sulphate for 24 hours postpartum and 558 were randomised to stopping the magnesium sulphate infusion immediately after delivery. Outcome measures: Primary outcome was the incidence of eclampsia in the first 24 hours postdelivery. Secondary outcomes included maternal death, maternal complications, time to start ambulation and time to start lactation. Results: The maternal characteristics at randomisation between the groups were not different. There were no differences in the rate of eclampsia; 1/555 (0.18%) versus 2/558 (0.35%) [relative risk (RR 0.7, 95% CI 0.1–3.3; P = 0.50] or maternal complications between the groups (RR 1.0, 95% CI 0.8–1.2; P = 0.76). Time to start ambulation was significantly shorter in the no magnesium sulphate group (18.1 ± 10.6 versus 11.8 ± 10.8 hours; P = 0.0001) and time to start lactation was equally shorter in the no magnesium sulphate group (24.1 ± 17.1 versus 17.1 ± 16.8 hours; P = 0.0001). Conclusions: Women with severe pre‐eclampsia treated with a minimum of 8 hours of magnesium sulphate before delivery do not benefit from continuing the magnesium sulphate for 24 hours postpartum. Tweetable abstract: No benefit of continuing magnesium sulphate postpartum in severe pre‐eclampsia exposed to this drug for a minimum of 8 hours before delivery. Abstract : Tweetable abstract No benefit of continuing magnesium sulphate postpartum in severe pre‐eclampsia exposed to this drug for a minimum of 8 hours prior to delivery.